2019
DOI: 10.1177/1550147719877616
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of artificial neural network architectures for building energy consumption forecasting

Abstract: Smart grids have recently attracted increasing attention because of their reliability, flexibility, sustainability, and efficiency. A typical smart grid consists of diverse components such as smart meters, energy management systems, energy storage systems, and renewable energy resources. In particular, to make an effective energy management strategy for the energy management system, accurate load forecasting is necessary. Recently, artificial neural network–based load forecasting models with good performance h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 48 publications
0
51
0
Order By: Relevance
“…However, the RICNN, which purposed a probabilistic approach, is a different purpose because we focus on day-ahead point load forecasting. In [36], the SELU-based ANN model with five hidden layers showed that the dataset we used in this study exhibited insufficient prediction accuracy compared to the other building types because its electric loads are close to zero. In [37], we proposed a two-stage electric load forecasting model to combine XGBoost and RF using MLR.…”
Section: Our Previous Workmentioning
confidence: 85%
See 3 more Smart Citations
“…However, the RICNN, which purposed a probabilistic approach, is a different purpose because we focus on day-ahead point load forecasting. In [36], the SELU-based ANN model with five hidden layers showed that the dataset we used in this study exhibited insufficient prediction accuracy compared to the other building types because its electric loads are close to zero. In [37], we proposed a two-stage electric load forecasting model to combine XGBoost and RF using MLR.…”
Section: Our Previous Workmentioning
confidence: 85%
“…The proposed RICNN model was verified using the electric energy consumption data of three large distribution complexes in South Korea. In [36], we constructed diverse ANN models using different numbers of hidden layers and diverse activation functions and compared their performances in a 30 min STLF resolution. To compare the prediction performance, we considered electric load data collected for two years from five different types of buildings (including the dataset used in this study).…”
Section: Our Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, short-term load forecasting (STLF) is a core technology of the EMS [9]; moreover, accurate electric load forecasting is required for stable and efficient smart grid operations [10]. From the perspective of a supplier, it is challenging to provide optimal benefits in a cost-effective analysis while storing a large amount of electric energy in the ESS; however, the smart 2 of 37 grid can plan effectively by predicting future electric energy consumption and receiving the required energy from internal and external energy sources [11]. It is also possible to optimize the renewable energy generation process [11,12].…”
Section: Introductionmentioning
confidence: 99%